2 × 2 MIMO Asymmetric U-Shaped Nonuniform Slot Antenna for the 4G LTE Metal-Housing Mobile Handsets. (28th December 2019) - Chen, I-Fong; Peng, Chia-Mei; Bao, Jing-Jing; Chen, Chia-Ching
Abstract : A 2 × 2 MIMO antenna for metal-housing mobile handset application is proposed in this article. The polarization diversity is used to arrange the two antennas' setup. The asymmetric U-shaped nonuniform slot antenna provides two different resonant bands are designed to be operated in long term evolution (LTE) covers lower band (698 MHz to 960 MHz) and upper band (1710 MHz to 2700 MHz). The modified type III balun is used for upper-operating band, and the open stub is used for lower-operating band, good impedance bandwidth, and radiated pattern and efficiency are shown. The isolation (S21) between the antennas is more than 20 dB, and the envelope correlation coefficient (ECC) is less than 0.02. A prototype of the proposed antenna chiselling in the metal-housing mobile handset (with 160 mm in length, 10 mm in height, and 70 mm in width) is fabricated and experimentally studied.